2019
DOI: 10.1128/iai.00540-18
|View full text |Cite
|
Sign up to set email alerts
|

PPE37 Is Essential for Mycobacterium tuberculosis Heme-Iron Acquisition (HIA), and a Defective PPE37 in Mycobacterium bovis BCG Prevents HIA

Abstract: Mycobacterium tuberculosis, one of the world’s leading causes of death, must acquire nutrients, such as iron, from the host to multiply and cause disease. Iron is an essential metal and M. tuberculosis possesses two different systems to acquire iron from its environment: siderophore-mediated iron acquisition (SMIA) and heme-iron acquisition (HIA), involving uptake and degradation of heme to release ferrous iron. We have discovered that Mycobacterium bovis BCG, the tuberculosis vaccine strain, is severely defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 77 publications
3
41
0
Order By: Relevance
“…We measured growth of the avirulent parent strain Mtb mc 2 6230 (H37Rv ΔRD1, ΔpanCD; S1 Table) and of Mtb ML1600 in self-made low-iron Middlebrook 7H9 medium using 20 μM ammonium ferric citrate (control), 10 μM human holo-transferrin, 10 μM human holo-lactoferrin, 5 μM human hemoglobin, 20 μM hemin, 0.2 μM mycobactin and 0.2 μM carboxymycobactin as sole iron sources, respectively. These experiments clearly showed that Mtb utilizes iron from mycobactin, carboxymycobactin, hemin and hemoglobin consistent with previous results [23,24,27,36]. In contrast, iron salts, transferrin and lactoferrin were only used in the presence of siderophores (Fig 1).…”
Section: Iron Sources Utilized By M Tuberculosissupporting
confidence: 91%
See 3 more Smart Citations
“…We measured growth of the avirulent parent strain Mtb mc 2 6230 (H37Rv ΔRD1, ΔpanCD; S1 Table) and of Mtb ML1600 in self-made low-iron Middlebrook 7H9 medium using 20 μM ammonium ferric citrate (control), 10 μM human holo-transferrin, 10 μM human holo-lactoferrin, 5 μM human hemoglobin, 20 μM hemin, 0.2 μM mycobactin and 0.2 μM carboxymycobactin as sole iron sources, respectively. These experiments clearly showed that Mtb utilizes iron from mycobactin, carboxymycobactin, hemin and hemoglobin consistent with previous results [23,24,27,36]. In contrast, iron salts, transferrin and lactoferrin were only used in the presence of siderophores (Fig 1).…”
Section: Iron Sources Utilized By M Tuberculosissupporting
confidence: 91%
“…Among those genes, we found that Mtb exhibits significantly stronger requirements for ppe37 and rv1085c encoding a hemolysin-like protein (Figs 3D and 8A; S7 and S9 Tables). The growth defect of Mtb mutants with insertions in ppe37 is consistent with previous findings that PPE37 is involved in heme utilization in the Mtb Erdman strain [27]. However, the requirement for Rv1085c for growth of Mtb in vitro in the absence of erythrocytes indicates that the molecular function of Rv1085c is probably different from that of hemolysins [49].…”
Section: Heme and Hemoglobin Utilization By M Tuberculosissupporting
confidence: 89%
See 2 more Smart Citations
“…The PPE‐PPW PPE20 and its cognate partner PE15 were experimentally identified as ESX‐3 substrates (Tufariello et al , ). Two other PPW proteins, PPE36 and PPE37, are also described to play a role in iron homeostasis through functions in heme‐iron acquisition (Mitra et al , ; Tullius et al , ). Together with sequence analysis of the EspG‐binding domain, these data render the hypothesis that PPE‐PPW proteins may be generally dependent on ESX‐3, rather than ESX‐5 for their translocation, increasingly likely (Abdallah et al , ; Korotkova et al , ; Tufariello et al , ).…”
Section: Secretion and Functions Of Specific Pe And Ppe Protein Subgrmentioning
confidence: 99%